Covid-19 issues in the official Speech Text of Malaysian Prime Minister on the Movement Control Order (MCO): semantic field analysis - Tazudin, Nor Aisyah Hafiza; Che Rodi, Rozita; Saimon, Aminuddin (Human Resource Management Academic Research Society, 2022)
In 2019, the world has been shocked by the emergence of an infectious virus called COVID-19. Due to the pandemic, the daily lifestyle of the people in the world has changed as they have to practice the new norms. Henceforth, many new terms and definitions that are rarely heard of before began to be used. However, these newly introduced terms might lead to confusion among the people which also could obstruct the messages from the government. Considering that, the researcher will focus on the application of Semantic Field Theory by Ullmann (1963) through the analytical model approach by Al-Attas (2001) in unravelling the meaning of the terms according to COVID-19 issues based on the speech text of the Malaysian Prime Minister on the Movement Control Order (MCO) in order to handle the pandemic. In the theory, five main aspects are being emphasized namely the focus word, key word, interwoven meaning, conceptional sphere and the formation of a semantic field. All of these aspects could unravel the complicated word meaning and at the same time show the real concepts that are tried to be conveyed by speakers and writers in a discourse. This study uses a qualitative approach. Researcher has investigated eight texts of the official speech by the Malaysian Prime Minister relating to MCO starting from 16th March 2020 until 11th January 2021. The result of the study shows that there are four main focus words namely safety, economy, education and health. From the focus words, other key words appear and surround the focus words which then form the conceptional sphere of COVID-19 in the Malaysian Prime Minister speech’s text on the MCO. For further research based on the knowledge about the COVID-19 issues, researcher perhaps can apply this theory directly into the study of other issues of the community.